2017
DOI: 10.1007/s41701-017-0007-x
|View full text |Cite
|
Sign up to set email alerts
|

“It Would Never Happen in My Country I Must Say”: A Corpus-Pragmatic Study on Asian English Learners’ Preferred Uses of Must and Should

Abstract: This paper aims to investigate Asian English learners' preferred uses of the modal auxiliaries must and should by using both syntactic, topical and semantic annotation as well as various corpus linguistic tools. Our primary goal is to identify culture-specific motivations in the use of the two modal verbs and to demonstrate how those relate to the use of the two items in language produced by L1 speakers of English. We adhere to Hinkel's study (TESOL Q 29(2):325-343. 1995(TESOL Q 29(2):325-343. , doi: 10.2307 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For instance, Hinkel"s (1995) analysis proposed that culture has an impact on the employment of modals between the English L1 speakers and Asian EFL learners. Confirming Hinkel"s main claim that Asian English learners" tendency to use the modals, should and must, is due to the cultural influence, compared to those forms used by the English L1 speakers, Kecskes & Kirner-Ludwig (2017) found that while both English native speakers and Asian English learners used the deontic modal should more the direct must, Asian English learners used must and should more purposefully than English natives, who appeared to apply them much more vaguely and polysemously. In the same line of research, Yang (2018) found that Chinese students tended to use modal verbs more frequently than professional researchers.…”
Section: Previous Researchmentioning
confidence: 56%
See 1 more Smart Citation
“…For instance, Hinkel"s (1995) analysis proposed that culture has an impact on the employment of modals between the English L1 speakers and Asian EFL learners. Confirming Hinkel"s main claim that Asian English learners" tendency to use the modals, should and must, is due to the cultural influence, compared to those forms used by the English L1 speakers, Kecskes & Kirner-Ludwig (2017) found that while both English native speakers and Asian English learners used the deontic modal should more the direct must, Asian English learners used must and should more purposefully than English natives, who appeared to apply them much more vaguely and polysemously. In the same line of research, Yang (2018) found that Chinese students tended to use modal verbs more frequently than professional researchers.…”
Section: Previous Researchmentioning
confidence: 56%
“…There is also a considerable body of literature on the use of English modal verbs by EFL learners with different L1 backgrounds (e.g., Hinkel, 1995Hinkel, , 2009Kecskes & Kirner-Ludwig 2017;Yang, 2018). For instance, Hinkel"s (1995) analysis proposed that culture has an impact on the employment of modals between the English L1 speakers and Asian EFL learners.…”
Section: Previous Researchmentioning
confidence: 99%
“…DeCapua and Huber (1995) highlighted the use of similar situations, softeners, downgraders, and mitigators as other strategies to be polite and support advice seekers' faces in advicegiving. Kecskes and Kirner-Ludwig (2017) noted a limited use of imperatives and verbs with strong illocutionary force to save the advice-seekers' faces and be polite and indirect. Morrow (2006) and Zeyrek (2001) suggested the inclusion of greetings in the openings and good or empathetic wishes and exclamations in the endings to form solidarity between the advice seeker and the advice giver.…”
Section: Advice Giving Strategies In Englishmentioning
confidence: 99%
“…For example, we used data from more than 1,500 speakers in producing Figure 1. To perform analysis on this scale, advanced computational technology is required to search through the data, compute frequencies, and provide statistical summaries such as those shown in the graph, which was produced using #LancsBox (Brezina et al, 2015; for an example of the program in use, see Kecskes & Kirner-Ludwig, 2017). Fourth, corpus findings are based on the observation of a very large number of examples of language use.…”
Section: Introductionmentioning
confidence: 99%